Skeletal Class Ⅱ Retrognathic Mandible Treated with Maxillary Single-jaw Surgery - YOSHIGA, DAIGO; KAWAMOTO, TATSUO; MIZUHARA, MASAHIRO; YOSHIOKA, IZUMI; SHIRAKAWA, TOMOHIKO; KUROISHI, KAYOKO; GUNJIGAKE, KAORI; MIYAMOTO, JUN J. (The Japanese Journal of Jaw Deformities, 2025)
Patients with skeletal Class Ⅱ malocclusion often undergo mandibular advancement surgery. However, to reduce stress on the mandibular condyle and temporomandibular joint, it is also possible to perform maxillary orthognathic surgery alone, planned with counterclockwise autorotation of the mandible to improve the relationship between the maxillary and mandibular jaws and occlusion. We herein report a case of successful treatment outcomes by performing maxillary orthognathic surgery alone in a patient with skeletal Class Ⅱ high-angle malocclusion. A 17-year-old female presented with complaints primarily related to chin retrusion and crowding, along with tension in the mentalis muscle during lip closure and a convex facial profile with a gummy smile. The diagnosis was skeletal Class Ⅱ malocclusion with significant clockwise rotation of the mandible and lingual inclination of the mandibular anterior teeth. The molar relationship was Angle Class Ⅰ, with an overjet of ＋5.0mm, overbite of ＋1.0mm, and arch length discrepancy of −1.0mm in the maxilla and −4.0mm in the mandible. After extracting both mandibular first premolars and conducting preoperative orthodontic treatment for 1 year 4 months, we performed maxillary horseshoe osteotomy combined with Le Fort Ⅰ osteotomy and genioplasty. The maxilla was moved 3.5mm upward in the anterior region and 4.5mm upward and 5.0mm backward in the molar region. As a result, the mandible rotated 3.5 degrees counterclockwise. Postoperative orthodontic treatment commenced immediately after surgery, and retention started thereafter. The tension in the mentalis muscle during lip closure decreased, resulting in a harmonious facial profile. Although the molar relationship became Class Ⅲ, satisfactory coverage and tight occlusion were achieved. At 5 years 6 months after the start of retention, a slight clockwise relapse of the mandible was observed, but good occlusion was maintained. Maxillary orthognathic surgery alone, by moving the maxilla upward and backward, resulted in counterclockwise rotation of the mandible, anterior movement of the chin, and an improved facial profile. In addition to the favorable treatment outcomes, the stability of the mid-term prognosis suggests that maxillary orthognathic surgery alone is an effective approach for Class Ⅱ skeletal malocclusion.